THE SPEECH ACTS OF REQUESTING HELP OF JAVANESE PEOPLE IN MALANG, EAST JAVA - Retno Setya Budiasningrum; Rahmi Rosita (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2021)
Requesting for help is one of illocutionary acts classified as a directive speech act. It performs by the speaker to get the interlocutor to do something. This study explored the expressions of requesting help used by Javanese people in Malang and the factors that influence them. This study described the speech act are used in asking for help in Javanese in Malang. It also presented the factors that influence these speech acts. The population in this study was the Javanese people in Malang. Some dialogues were taken randomly in different places with participants who have various backgrounds. The patterns of speech acts used in asking for help are very diverse. The factors that influenced their diversity are closeness, position, age, educational background, and norms of politeness.